Helmintofauna de Chelonia mydas (Linnaeus, 1758) no sul do Estado do Espírito Santo e descrições de lesões teciduais. - Binoti, Érika (2015)
Among the species of sea turtles that exist, all are classified under some degree of extinction, including the five species that occur along the Brazilian coast. The threats are many, including the anthropic action, and one of the illnesses that make them appear dead or weakened on the beaches, is the parasitism. Due to lack of knowledge about the pathogens that affect these animals, the objective of this study to evaluate the helmintofauna of sea turtles Chelonia mydas who came to death in the southern coast of the State of Espírito Santo and describe tissue lesions in animals parasitised. We conducted a retrospective study using 212 chips of turtles that were necropsiadas. And a prospective study, where the 212 turtles, 50 arasitized were selected for gathering samples of parasites, and 16 for sample collection of fabrics. A total of 106 turtles presented one or more species of parasites. 21 different species have been identified and a genus of flukes spread across nine families. Among the species identified, three of them are reported for the first time in the Brazilian coast, Deuterobaris intestinalis, Enodiotrema reductum and Rhytidodoides similis. There was no significant association of parasitism with debilitated animals. The tissue assessed in histopathological examination, although eggs have been observed, associated or not to giant cells in various organs, mainly in spleen and lungs. However, the lesions by eggs were not related to weakness or death of animals and it was not possible to say that the eggs belonged to Spirorchiidae family, due to chronic injuries and the adult parasites of this family have been found in all animals presented the eggs in the tissues. These results contribute so important for the knowledge of the helmintológica fauna of sea turtles off the coast of Espírito Santo